The Many Unknowns Concerning the Bioenergetics of Exhaustion and Senescence during Chronic Viral Infection - Schurich, Anna; Henson, Sian M. (Frontiers in Immunology, 2014)
The immune system cannot be continuously reactivated throughout the lifetime of an organism, there is a finite point at which repeated antigenic challenge leads to the loss of lymphocyte function or the cells themselves. Antigen-specific T cells can be compromised in two ways through the distinct processes of replicative senescence and exhaustion. Senescence is initiated by a DNA damage response whereas exhaustion triggers inhibitory receptors to dampen the immune response. These two distinct pathways not only differ in their initiation but growing evidence suggests that their bioenergetics is also different. We review here recent findings uncovering the metabolism of these unique states.